Visualization and Debugging of Concurrent Java Programs with UML - Mehner, Katharina; Weymann, Bernd (Proceedings of the Workshop on Software Visualization (satellite event of the International Conference on Software Engineering - ICSE 2001), Toronto (Canada))

Improving Goodput by Relaying in Transmission-Power-Limited Wireless Systems - Mengesha, Seble; Karl, Holger; Wolisz, Adam (GI Jahrestagung (1))

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, Cedrik; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Players, Playthings and Patterns: Three Stages of Heteronomy in Beckett's Mature Drama - Tönnies, Merle (Samuel Beckett Today / Aujourd'hui: Endlessness in the Year 2000 / Fin sans fin en l'an 2000)

The Limits of Defining Power in Terms of Exclusion - Tönnies, Merle (Common Ground? Crossovers between Cultural Studies and Postcolonial Studies)

Schwingungsanalyse verstimmter Schaufelkränze mit Reibelementen - Panning, Lars; Sextro, Walter; Popp, Karl (Schwingungen in rotierenden Maschinen VI SIRM, Referate der Tagung in Wien)

Heat and Wear Generation for Rolling Contacts - Sextro, Walter (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Development and Experimental Validation of a Point Contact Model for Dynamical Problems with Friction - Sextro, Walter (ASME Design Engineering Technical Conferences)

Localization in Nonlinear Mistuned Systems with Cyclic Symmetry - Sextro, Walter; Popp, Karl; Krzyzynski, Tomasz (Nonlinear Dynamics)
In forced systems with cyclic symmetry localization can occur due toparameter uncertainties. Often, Monte-Carlo simulations are used to findregions, where the system response is sensitive to parameteruncertainties. These simulations require a large computation time.Therefore, an approximate method to calculate the envelopes of thefrequency response functions is developed in this paper. An example of anonlinear system with cyclic symmetry is a bladed disk assembly withfriction dampers. Friction dampers can be installed underneath the bladeplatforms of turbine blades. Due to dry friction and the relative motionbetween blades and dampers, energy is dissipated, which results in areduction of blade vibration amplitudes. By optimizing the mass of thefriction dampers, the best damping effects are obtained, which lead toan increase in the reliability of the turbine. In this paper, thecalculated response of a mistuned bladed disk assembly with frictiondampers is discussed. An approximate method is developed to calculatethe envelopes of the corresponding frequency response function forstatistically varying eigenfrequencies of the blades. Regions wherelocalization can occur with a high probability, are calculated by thismethod.
Keywords: bladed disk assembly; mistuning; sensitivity; localization

Piezoelektrische lineare Schwingungsantriebe - Wallaschek, Jörg; Hemsel, Tobias (Special Antriebstechnik)

Analysing capacity improvements in wireless networks by relaying - Karl, Holger; Mengesha, Seble (Proc. of IEEE Intl. Conf. on Wireless LANs and Home Networks)

Relative jitter packet scheduling for differentiated services - Quynh, T; Karl, Holger; Wolisz, Adam; Rebensburg, Klaus (Proc. 9th IFIP Conf. Perf. Modeling and Eval. of ATM & IP Networks)

The promise of workplace training for non-college-bound youth: Theory and evidence from German apprenticeship - Clark, Damon; Fahr, Rene (CEP Discussion Paper No. 528)

Komponentenorientierte Softwareentwicklung in Softwareunternehmen: Konzeption eines Vorgehensmodells zur Einführung und Etablierung - Schryen, Guido

British Political Speeches from Churchill to Blair

The randomized z-buffer algorithm - Wand, Michael; Fischer, Matthias; Peter, Ingmar; Meyer auf der Heide, Friedhelm; Straßer, Wolfgang (Proceedings of the 28th annual conference on Computer graphics and interactive techniques - SIGGRAPH '01)
We present a new output-sensitive rendering algorithm, the randomized z-buffer algorithm. It renders an image of an arbitrary three-dimensional scene consisting of triangular primitives by reconstruction from a dynamically chosen set of random surface sample points. This approach is independent of mesh connectivity and topology. The resulting rendering time grows only logarithmically with the numbers of triangles in the scene. We were able to render walkthroughs of scenes of up to 10^14 triangles at interactive frame rates. Automatic identification of low detail scene components ensures that the rendering speed of the randomized z-buffer cannot drop below that of conventional z-buffer rendering. Experimental and analytical evidence is given that the image quality is comparable to that of common approaches like z-buffer rendering. The precomputed data structures employed by the randomized z-buffer allow for interactive dynamic updates of the scene. Their memory requirements grow only linearly with the number of triangles and allow for a scene graph based instantiation scheme to further reduce memory consumption.

Data Management in Networks - Meyer auf der Heide, Friedhelm (Graph-Theoretic Concepts in Computer Science)

Parallel Bridging Models and Their Impact on Algorithm Design - Meyer auf der Heide, Friedhelm; Wanka, Rolf (Computational Science - ICCS 2001)

The Algorithms Behind GAIO — Set Oriented Numerical Methods for Dynamical Systems - Dellnitz, Michael; Froyland, Gary; Junge, Oliver (Ergodic Theory, Analysis, and Efficient Simulation of Dynamical Systems)

Extracting Dynamical Behavior via Markov Models - Froyland, Gary (Nonlinear Dynamics and Statistics)